PENGARUH EMPLOYEE ENGAGEMENT DAN EMPLOYEE SATISFACTION TERHADAP KINERJA KARYAWAN - Rahmadani, Nadya Jasmine; Kurniawati, Desi Tri (Jurnal Kewirausahaan dan Inovasi, 2022)
The objective of this quantitative research is to identify the partial and simultaneous effects of employee engagement and employee satisfaction on employee performance at PT. Shopee International Indonesia Surabaya. The data was acquired from questionnaires distributed to the entire 98 employees and was analyzed using multiple linear regression in SPSS ver. 25. Validity and reliability testing was conducted on each item of the research variables. This study finds that employee engagement (X1) and employee satisfaction (X2) partially influence employee performance and that employee engagement (X1) and employee satisfaction (X2) simultaneously affect employee performance at PT. Shopee International Indonesia Surabaya.